Basis-teoretiese perspektiewe op dissipelskap en die verhouding tot gemeentebou - Steyn, Karel P. (HTS teologiese studies, 2015)
Basis-theoretical perspectives on discipleship and its relation towards congregation building. In recent times there has been a growing focus on the process of building up the local church in the Reformed Churches of South Africa. Congregation building should not only take place through growing numbers, but also through spiritual growth. In this article a few basis-theoretical perspectives will be explored through a study of applicable literature, regarding the definition of ‘disciple’ and ’discipleship’. It is also the purpose of this article to establish whether or not there is any relation between discipleship and congregation building. It is the premise of this article that discipleship, with the basis-theoretical perspectives in mind, can suffice as a ministry model towards congregation building for the church in the ever so changing times in which she finds herself when the kingdom of God is taken as the goal of discipleship, and love for God and your neighbour is taken as the underlying principle of discipleship.